(untitled) (Bangladesh Journal of Pharmacology, 2013)
In the present study, we evaluated the protective effects of the aqueous-methanolic extract of Suaeda fruticosa (500 mg/kg and 750 mg/kg b.w., p.o) against paracetamol-induced hepatotoxicity in rabbits. Silymarin 100 mg/kg, p.o. was served as standard. The degree of protection was determined by measuring the levels of biochemical marker such as SGOT, SGPT, ALP and bilirubin (total). The results showed that extract of S. fruticosa significantly (p<0.05) decreased the paracetamol-induced increased levels of liver enzymes and total bilirubin in a dose dependent manner. Histopathological studies also revealed the hepatoprotective effects of S. fruticosa. It is concluded that the aqueous-methanolic extract of S. fruticosa possesses hepatoprotective activity.